Serum cytokines and steroidal hormones in polymyalgia rheumatica and elderly-onset rheumatoid arthritis. Issue 11 (27th April 2006) - Cutolo, M; Montecucco, C M; Cavagna, L; Caporali, R; Capellino, S; Montagna, P; Fazzuoli, L; Villaggio, B; Seriolo, B; Sulli, A
Abstract : Background: Polymyalgia rheumatica (PMR) may create some difficulties in the differential diagnosis of elderly-onset rheumatoid arthritis (EORA) and of EORA with PMR-like onset (EORA/PMR). Aim: To investigate possible differences between three groups of patients, with regard to serum levels of inflammatory cytokines and steroidal hormones at baseline and after 1 month of treatment with glucocorticoids (prednisone 7.5–12.5 mg/day). Patients and methods: 14 patients with PMR, 15 with EORA and 14 with EORA/PMR, as well as 15 healthy, matched controls were analysed. Tumour necrosis factor α (TNFα), interleukin (IL)6, IL1 receptor antagonist (IL1Ra), cortisol, dehydroepiandrosterone sulphate (DHEAS) and 17-hydroxy-progesterone (PRG) were evaluated. Results: Serum levels of both TNFα and IL6 were significantly higher in all three groups of patients than in controls (p<0.01). Serum IL6 levels were significantly higher in patients with both PMR and EORA/PMR than in patients with EORA (p<0.05). IL1Ra serum levels were significantly higher in patients with EORA than in controls (p<0.001) and in patients with PMR and EORA/PMR (p<0.05). DHEAS was significantly lower in patients with EORA/PMR than in those with EORA (p<0.05). PRG was significantly higher in all patient groups (p<0.05). After glucocorticoid treatment, serum TNFα and IL6 levels significantly decreased in all patient groups; IL1Ra significantly increased in patients with PMR and in those with EORA/PMR; cortisol, DHEAS, and PRG significantly decreased in patients with PMR and in those with EORA/PMR (p<0.05). Conclusions: Different cytokine and steroidal hormone patterns suggest that patients with PMR and those with EORA/PMR seem to be have a more intensive inflammatory reaction and are more efficient responders to glucocorticoid treatment than patients with EORA.